THE CORRELATION BETWEEN MOTIVATION AND READING COMPREHENSION OF THE SECOND YEAR STUDENTS OF SMA NEGERI 4 TAPUNG - Sari, Putri Kurnia; Azhar, Fadly; Ras, Fakhri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to identify the level of motivation in reading comprehension of the second year students’ of SMA Negeri 4 Tapung, to recognize the level of reading comprehension ability the second year students’ of SMA Negeri 4 Tapung, and to find out if there is a significant correlation between motivation and reading comprehension of the second year students of SMA Negeri 4 Tapung. The sample of this research consisted of 38 students which were taken by using Total Sampling Technique. The data were collected through a set of questionnaire to measure students’ motivation and test to measure students’ reading comprehension. The research findings revealed that the motivation of the second year students of SMA Negeri 4 Tapung is categorized into high level (36.9%). The reading comprehension ability of the second year students of SMA Negeri 4 Tapung is categorized into good level (55.3%). Pearson’s Product Moment Formula was used to correlate both motivation (variable X) and reading comprehension (variable Y). The result showed that there was a statistically significant correlation (0.650) between the students’ motivation and their reading comprehension. In short, there is a significant correlation between motivation and reading comprehension of the second year students of SMA Negeri 4 Tapung.Key Words: Correlation, Motivation, Reading Comprehension